EQ, PERSEPSI SISWA TENTANG POLA ASUH ORANG TUA DAN KEMANDIRIAN BELAJAR - Endah Prahesra; I Komang Winatha; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2015)
This study aims at determining the effect of the emotional intelligence, student perceptions about parenting parents and independent learning on the results of integrated social studies. The method used is descriptive approach verification ex post facto. The population in this study is all students of eighth grade of 184 students and the sample in this study is 125 students. The sampling technique is using probability sampling with simple random sampling. The results shows: There is an effect of emotional intelligence of students on learning achievement of social studies. There is an influence of students perceptions about parenting parents of students on learning achievement of social studies. There is an influence of students independent learning on learning achievement of social studies. There is an influence of emotional intelligence, student perceptions about parenting parents and independent learning on learning achievement of social studies.Tujuan penelitian untuk mengetahui pengaruh kecerdasan emosional, persepsi siswa tentang pola asuh orang tua dan kemandirian belajar terhadap hasil belajar IPS Terpadu. Metode yang digunakan adalah deskriptif verifikatif dengan pendekatan ex post facto. Populasi dalam penelitian berjumlah 184 siswa dan sampelnya berjumlah 125 siswa. Teknik pengambilan sampel menggunakan probability sampling dengan simple random sampling. Hasil penelitian menunjukkan bahwa: Ada pengaruh kecerdasan emosional siswa terhadap hasil belajar IPS Terpadu. Ada pengaruh persepsi siswa tentang pola asuh orang tua siswa terhadap hasil belajar IPS Terpadu. Ada pengaruh kemandirian belajar siswa terhadap hasil belajar IPS Terpadu. Ada pengaruh kecerdasan emosional, persepsi siswa tentang pola asuh orang tua dan kemandirian belajar terhadap hasil belajar IPS Terpadu.Kata kunci: hasil belajar, kecerdasan emosional, kemandirian belajar